Engineering Design and Ergonomic Evaluation of an Assistive Device for Manual Material Handling - Nasution, Andri Rachmat Kumalasian; Ramadhanti, Ledina; Fauziah, Anisa; Puspita, Hermita Dyah (Tibuana, 2026)
Manual material handling (MMH) remains a major contributor to work-related musculoskeletal disorders in manufacturing environments. This study proposes and evaluates an assistive device for box panel handling aimed at reducing ergonomic risk during lifting and transport operations at PT. XYZ. A case-study approach was employed using multiple ergonomic assessment methods, including the Nordic Body Map (NBM), Rapid Entire Body Assessment (REBA), the Revised NIOSH Lifting Equation (RNLE), and the Snook Tables. Baseline results indicated dominant lower-back (77%) and upper-back (71%) complaints, a high-risk REBA score of 12, low recommended weight limits (4.46–4.91 kg), and excessive lifting indices (5.50–6.05) for a maximum load of 37 kg. The Snook analysis yielded a maximum acceptable weight of 13.0 kg with a load-to-MAW ratio of 1.38. A trolley-based assistive device integrating lifting and transfer support was then designed to minimize trunk flexion and eliminate manual carrying during transport. Post-intervention evaluation showed substantial improvements, with the REBA score reduced to 1, lifting indices below unity, and the load-to-MAW ratio approaching zero. These results demonstrate that engineering controls in the form of practical assistive devices can effectively reduce ergonomic risk and improve manual material handling safety in industrial settings.